Daily field checking list by Walter Rosene, March 27, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Bob Walker, March 27, 1937. Also notes there was food in the Great Horned Owl nest. Plustek--flatbed